2021
DOI: 10.3390/ijerph182010809
|View full text |Cite
|
Sign up to set email alerts
|

Do Blood Lactate Levels Affect the Kinematic Patterns of Jump Shots in Handball?

Abstract: The aim of this study was to determine whether the dynamic motor stereotype of movement (shooting technique) is violated under conditions of an increased lactate concentration in a player's blood after a 30–15 intermittent fitness test. The hypotheses was that there would be statistically significant differences in ball speed and shooting accuracy in jump shots on the goal before and after the occurrence of fatigue in the player. The sample of respondents consisted of 10 top-level handball players of the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…This decreased the kinetic transport that reaches the ball, which leads to a decrease in its speed and consequently its accuracy. This is consistent with studies by Nuno et al (2016); Belcic et al (2021), who indicated that muscle fatigue associated with an increase in the concentration of lactic acid in the blood affects the performance variables of mechanical shooting in handball players, while the accuracy of the shooting is the final result of performance. This is normal since the intensity has an impact on the mechanical factors, which in turn has an impact on accuracy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This decreased the kinetic transport that reaches the ball, which leads to a decrease in its speed and consequently its accuracy. This is consistent with studies by Nuno et al (2016); Belcic et al (2021), who indicated that muscle fatigue associated with an increase in the concentration of lactic acid in the blood affects the performance variables of mechanical shooting in handball players, while the accuracy of the shooting is the final result of performance. This is normal since the intensity has an impact on the mechanical factors, which in turn has an impact on accuracy.…”
Section: Discussionsupporting
confidence: 93%
“…In terms of lactic acid, the handball game combines aerobic and anaerobic energy systems due to the long playing time, which is an hour of uninterrupted play, and a transition to handball skills that are performed quickly with high intensity. These conditions increase the likelihood of lactic acid concentration in the blood, and the effect of this increase is visible when performing skills that require speed and strength, such as shooting the ball into the goal (Belcic et al, 2021). The physiological demands of handball, which are based on the aerobic and anaerobic systems, contribute significantly to an increase in lactic acid concentration in the blood (Chaouachi, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Belcic at al. (2021) reported that the fast break is the decisive factor of success in handball teams competing in the same league; moreover, Bilge (2012) earlier found that the tactical choice of fast breaks leads to victory.…”
Section: Discussionmentioning
confidence: 99%
“…The studies indicate that, at the professional national levels, the full-step cycle, with three previous steps, is the most used [16][17][18]. However, in the modern international game of handball, the mobility of the defense players is continuously increasing, leading to more open defensive systems, and positioning the attacking players further away from the goal area than in traditional handball defenses.…”
Section: Introductionmentioning
confidence: 99%